2012
DOI: 10.1007/s00381-012-1875-9
|View full text |Cite
|
Sign up to set email alerts
|

Risk and protective factors of intraventricular hemorrhage in preterm babies in Wuhan, China

Abstract: In the present study, factors that related to neonatal IVH included hypotension, prenatal steroid use, and transportation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0
4

Year Published

2014
2014
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 19 publications
1
17
0
4
Order By: Relevance
“…For the two case control studies, one found that cesarean sections were associated with lower cord blood plasmin activity and lower umbilical blood IgG, IgM, C3, and C4 compared to vaginal delivery 51. The second case control study, making the same comparisons, found no association between cesarean birth and intraventricular hemorrhage 52. The eleven cross-sectional studies consistently found that cesarean sections were associated with higher risks of venous thromboembolism, surgical site infection, and postpartum infection.…”
Section: Consequences Of Cesarean Sectionsmentioning
confidence: 86%
“…For the two case control studies, one found that cesarean sections were associated with lower cord blood plasmin activity and lower umbilical blood IgG, IgM, C3, and C4 compared to vaginal delivery 51. The second case control study, making the same comparisons, found no association between cesarean birth and intraventricular hemorrhage 52. The eleven cross-sectional studies consistently found that cesarean sections were associated with higher risks of venous thromboembolism, surgical site infection, and postpartum infection.…”
Section: Consequences Of Cesarean Sectionsmentioning
confidence: 86%
“…48,55,66,[83][84][85][86][87] Eight observational studies (low-quality, downgraded for indirectness) found no association between hypothermia and IVH. 43,60,61,[88][89][90][91][92] For the important outcome of respiratory issues, there is evidence from 9 observational studies 44,48,50,67,83,[93][94][95][96] (low-quality evidence) showing an association between hypothermia and respiratory disease. One large randomized controlled trial 79 (low-quality evidence, downgraded for imprecision and risk of bias) found a reduction in pulmonary hemorrhage associated with improved admission temperature (OR, 0.57; 95% CI, 0.35-0.94).…”
Section: Consensus On Sciencementioning
confidence: 99%
“…48,55,66,[83][84][85][86][87] Eight observational studies (lowquality, downgraded for indirectness) found no association between hypothermia and IVH. 43,60,61,[88][89][90][91][92] For the important outcome of respiratory issues, there is evidence from 9 observational studies 44,48,50,67,83,[93][94][95][96] (lowquality evidence) showing an association between hypothermia and respiratory disease. One large randomized controlled trial 79 (low-quality evidence, downgraded for imprecision and risk of bias) found a reduction in pulmonary hemorrhage associated with improved admission temperature (OR, 0.57; 95% CI, 0.35-0.94).…”
Section: Consensus On Sciencementioning
confidence: 99%